2021
DOI: 10.1155/2021/4839077
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Population Median under Robust Measures of an Auxiliary Variable

Abstract: In this paper, a generalized class of estimators for the estimation of population median are proposed under simple random sampling without replacement (SRSWOR) through robust measures of the auxiliary variable. Three robust measures, decile mean, Hodges–Lehmann estimator, and trimean of an auxiliary variable, are used. Mathematical properties of the proposed estimators such as bias, mean squared error (MSE), and minimum MSE are derived up to first order of approximation. We considered various real-life dataset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…On the other hand, it is also observed that the [8,9] estimators are more efficient than our proposed class of estimators, even at optimality conditions. This is indicated as the Mean squared errors of these estimators are less than the proposed class of estimators in the four populations.…”
Section: Plos Onementioning
confidence: 66%
See 4 more Smart Citations
“…On the other hand, it is also observed that the [8,9] estimators are more efficient than our proposed class of estimators, even at optimality conditions. This is indicated as the Mean squared errors of these estimators are less than the proposed class of estimators in the four populations.…”
Section: Plos Onementioning
confidence: 66%
“…From the works of [ 9 ] their proposed estimators are more efficient than [ 8 ] estimator. Therefore, [ 9 ] estimators are more efficient than proposed estimator.…”
Section: Efficiency Comparisonsmentioning
confidence: 99%
See 3 more Smart Citations